Environmental and social dimensions for sustainability of business, economics and finances - Wijeyaratne, M.J.S. (UAE and University of Kelaniya, 2015)
The human species, Homo sapiens has become the most intelligent and the most superior creature of the world due to its well-developed brain resulting in high intelligence. This high intelligence had helped him to generate knowledge and transfer it to the next generation. In any field, generation of knowledge is done through research. The findings of research are disseminated through various forms so that the present generations and future generations can use those for their wellbeing to make a better tomorrow. Today, in an era of knowledge based economy, research in the fields of Business, Management, Economics and Finance are of utmost importance to achieve sustainable economic development. Sri Lanka, after a 30 year long secessionist internal war with a minority rebellion group is aiming at rapid economic development. The aim of every person is to live in better life tomorrow than yesterday. In an era of “beyond the Millennium Development Goals”, the United Nations is emphasizing on continuous efforts to achieve prosperity, equity, freedom, dignity and peace for everybody. According to the UN, post-millennium development goals consultations have emphasized a global development agenda beyond 2015, where sustainable development is a key consideration (UN 2013).